PARENT INVOLVEMENT FOR ENGLISH LEARNING SUCCESS: SYSTEMATIC REVIEW - Riski, Yunita Ayu; Indah, Rohmani Nur; Toyyibah, Toyyibah (PROJECT (Professional Journal of English Education), 2024)
The role of parents in English language learning success has been an important topic in various educational studies. This systematic literature review aims to identify and analyze the research that has been conducted on how parental involvement affects children's achievement in English language learning. Through a comprehensive analysis of multiple sources, this research seeks to provide a clear picture of the contribution of parents in supporting learning and the factors that influence the effectiveness of their involvement. The method of this research used a Systematic Literature Review. The selection of the inclusion and exclusion criteria has been determined. It found 86 which was then selected into 13 studies obtained from two databases, ERIC and Connectedpapers. This study analyzes the characteristics of the studies, the impact of parent involvement for learning English success, the pattern of parental involvement, and the guidelines and strategies of the ideal parent involvement in Indonesia. The results of this study showed that parent involvement has a significant positive impact on the English learning success.